Proceedings of the 24th International Conference on Machine Learning 2007
DOI: 10.1145/1273496.1273569
|View full text |Cite
|
Sign up to set email alerts
|

Discriminant analysis in correlation similarity measure space

Abstract: Correlation is one of the most widely used similarity measures in machine learning like Euclidean and Mahalanobis distances. However, compared with proposed numerous discriminant learning algorithms in distance metric space, only a very little work has been conducted on this topic using correlation similarity measure. In this paper, we propose a novel discriminant learning algorithm in correlation measure space, Correlation Discriminant Analysis (CDA). In this framework, based on the definitions of within-clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 22 publications
1
58
0
Order By: Relevance
“…This is used to describe similarities between two vectors. This is used in pattern recognition, multivariate statistics ISSN 1948-5433 2016 and data mining (Ma et al, 2007).…”
Section: Correlationmentioning
confidence: 99%
“…This is used to describe similarities between two vectors. This is used in pattern recognition, multivariate statistics ISSN 1948-5433 2016 and data mining (Ma et al, 2007).…”
Section: Correlationmentioning
confidence: 99%
“…It is worth noting that the use of the PCA here is not critical in the sense that any unsupervised subspace learning method such as Kernel PCA, 2DPCA [34], [35], LLE [36], LPP [37] CDA [38], CEA [39], kd-tree, and random projection tree [29] can be used. Denoting F as the feature representation, we measure the similarity score by MCS between two images.…”
Section: Face Verification By Binary-like Representation and Mcsmentioning
confidence: 99%
“…Earlier works such as [9,10] have shown that correlation based metrics perform better than the conventional Euclidean and Mahalanobis distances for classification and learning tasks. Motivated by the effectiveness of correlation-based similarity measures, we propose to use cosine similarity for change detection.…”
Section: Technical Detailsmentioning
confidence: 99%
“…To summarize the operation of the overall algorithm, given the reference image and the target image, we first calculate the LSK from both the reference image and the registered target image at all pixel locations. Comparison between LSKs computed from two images is carried out using the cosine similarity measure [9,10]. This step produces a "dissimilarity map" showing the likelihood of dissimilarity between the reference and target images.…”
Section: Introduction and Overviewmentioning
confidence: 99%